Use of seismic surface wave testing to assess track substructure condition. (30th November 2017) - Sussmann, T.R.; Thompson, H.B.; Stark, T.D.; Wilk, S.T.; Ho, C.L.
Highlights: Seismic surface testing evaluates the modulus with depth at various railroad track locations. The BSPA is capable of measuring the ballast modulus underneath railroad ties and within the crib. The ballast modulus of fouled ballast decreases by a factor of two when exposed to moisture. Abstract: This paper describes the use of Spectral Analysis of Surface Wave (SASW) for characterizing rail track ballast and foundation layers. Surface wave testing on a rail track is more complicated than on soil sites or pavements due to the presence of large ballast void spaces, crossties, and rails as well as the complex variation of shear-wave velocity and Young's modulus with depth. Young's modulus is presented for both clean and fouled ballast in wet and dry conditions using the results of surface wave testing and SASW. Young's modulus can be used to assess tie and track support at different locations, e.g. tie center and edge, under the applied loads. A portable surface wave system is described as well as its expansion to measure Young's modulus under two ties in the same test.